Improving data management at recycle center by using waste management system - Koh, Xin Yin; Hafit, Hanayanti (Penerbit UTHM, 2021)
Recycle center is a company that responsible for collecting recyclable material and sells recyclable material after classified the waste to other manufacturers. For instance, Beyn Newman Waste Solution recycle center is managing varieties of recyclable materials such as paper, plastic, aluminum, bottle, iron and so on. Currently, the Beyn NewMan Waste Solution recycle center uses the waste management system for storing the waste information and sales order. However, the current system consists of several issues that need to be optimized in terms of waste material management, lack of sales report function and low efficiency. Thus, the proposed system is developed to help overcome these limitations. The proposed system has seven modules which are the login module, manage user module, waste attribute module, waste category module, waste material module, sales order module and sales report module. This system is developed by using the waterfall model methodology. The proposed system is written by using PHP programming language and the developed platform is Microsoft Expression Web 4. XAMPP is being used as a database server. Beyn NewMan Waste Solution recycle center as the target to take part in the user acceptance test(UAT) after the developed system is released. The expected outcome of the proposed system is waste material information become wellorganized, enhance the system’s efficiency by adding the manage user function and having the sales report function.